The Impact of Employee Satisfaction on Innovation Capacity in Telecommunications - Anes Hrnjic; Irma Djidelija (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
The dominant feature of today's business environment is accelerated dynamics and dramatic change intensity which significantly influences the life cycle of strategy, business orientation and individual employee operations. These trends require continuous adjustment of business philosophy through innovation in various contexts acting as key drivers for successful handling of change and implementation of innovative ideas. Recent research shows that 39.9% of employed citizens within EU operate in the services sector while it accounts for 46.2% of added value creation in the EU market. Telecommunications are one of the major segments of services sector and people working for telecom operators represent the crucial asset in innovation management in the particular industry. Organizational behavior in terms of innovation is determined by various factors, whose number, direction and intensity is not yet clearly defined. Research aims to explore the impact of job satisfaction on innovative capacity of telecom operators in Bosnia and Herzegovina evaluating efficacy of HRM (human resource management) practices in the process of creating and implementing innovation. Methodology consists of two appropriate instruments for evaluation of job satisfaction and employee innovative behavior and primary data was analyzed using linear regression method. Limitations of the study are discussed and recommendations for future research of job satisfaction impact on employee innovative behavior are given. Practical implications on how to stimulate innovation in the organizational context are states in the discussion and conclusion.
Keywords: L96; J28; O30; 330; employee satisfaction; innovation; telecommunications; HRM